2013
DOI: 10.1371/journal.pone.0066373
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia-Host Interactions: Host Mating Patterns Affect Wolbachia Density Dynamics

Abstract: Wolbachia are maternally inherited intracellular bacteria that infect a wide range of arthropods and cause an array of effects on host reproduction, fitness and mating behavior. Although our understanding of the Wolbachia-associated effects on hosts is rapidly expanding, our knowledge of the host factors that mediate Wolbachia dynamics is rudimentary. Here, we explore the interactions between Wolbachia and its host, the two-spotted spider mite Tetranychus urticae Koch. Our results indicate that Wolbachia induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 53 publications
3
42
2
Order By: Relevance
“…At the beginning of this project, phylogenetic analyses of Wolbachia 16S ribosomal RNA (rRNA) genes and multilocus sequence typing (MLST) showed that the Wolbachia from T. urticae belonged to supergroup B (Fig. S1; Zhao et al, ). The number of eggs deposited by the CI cross [female uninfected (U) × male infected (I)] was similar to the number deposited by the Wolbachia ‐uninfected (WU) crosses (female U × male U) (WU vs. CI = 33.2 ± 8.92 vs. 33.4 ± 9.98, mean ± SD, P = 0.999, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning of this project, phylogenetic analyses of Wolbachia 16S ribosomal RNA (rRNA) genes and multilocus sequence typing (MLST) showed that the Wolbachia from T. urticae belonged to supergroup B (Fig. S1; Zhao et al, ). The number of eggs deposited by the CI cross [female uninfected (U) × male infected (I)] was similar to the number deposited by the Wolbachia ‐uninfected (WU) crosses (female U × male U) (WU vs. CI = 33.2 ± 8.92 vs. 33.4 ± 9.98, mean ± SD, P = 0.999, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that Wolbachia 's effects on host fecundity vary distinctly amongst different populations of T. urticae , including deleterious (Vala et al, ; Vala et al, ), neutral (Vala et al, ; Xie et al, ; Zhao et al, ) and beneficial effects (Xie et al, ; Sun et al, ). In our study, Wolbachia ‐induced CI killed the females in the offspring of the CI cross.…”
Section: Discussionmentioning
confidence: 99%
“…Nine Wolbachia strains were detected from the positive specimens, and several of these strains have previously been studied in detail. For example, there is evidence that Wolbachia induces CI in several spider mites, including T. urticae 323343, T. phaselus 26, T. truncatus 27, T. piercei 8 and A. viennensis 35. Regarding Cardinium , it was found to induce CI in T. piercei 8, T. phaselus 26 and T. truncatus 27.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitic behavior of intercellular bacteria with invertebrates are very common and play an important role to manipulate host biological interactions such as reproductions, developments, gene expression (Zhao et al, 2013) and immune systems (Ivanov & Littman, 2011). A bulk of researches have been conducted to identified the insectbacteria association particularly Wolbachia exerts negative impacts to reduce host fitness, responsible for degradation and early death (Min & Benzer, 1997), responsible for pathogen dissemination (Cook et al, 2008), reduce host survival rate (McMeniman et al, 2009), manipulate reproductive system (McGraw et al, 2001) and inhibit the pathogenicity of host .With these above reproductive manipulations, the bacterium (Wolbcahia) thrives in its various hosts at the expense of the hosts' reproduction and act like reproductive parasite to reduced host populations successfully.…”
Section: Induction Of Parthenogenesismentioning
confidence: 99%
“…It is beneficial for the host species (Taylor et al, 2013) by increasing the survival rate of host or insect species (Vala et al, 2003;Dobson et al, 2004;Foster et al, 2005;Weeks et al, 2007;Zhao et al, 2013) or enhancing the fecundity rate (Girin & Bouletreau, 1995;Dobson et al, 2002a;Fry et al, 2004;Xie et al, 2011). In Tribolium confusum (Coleoptera: Tenebrionidae) infected male sperm with Wolbachia takes long reproductive time than compared to uninfected ones.…”
Section: Mutualistic Role Of Wolbachiamentioning
confidence: 99%